The k- and c-reflexivity of locally convex vector spaces - Brudovski, B. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. С. Брудовский. О к- и с-рефлексивности локально выпуклых пространствB. Brudovskis. Apie lokaliai iškilių erdvių k- ir c- refleksivumą